2014
DOI: 10.1177/0145482x1410800108
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Artworks for People who Are Blind or Visually Impaired Using Raised Printing

Abstract: Everyone has the right to freely participate in the cultural life of the community (United Nations, 2012). In Europe and around the globe, many efforts have been made in order to include people with visual impairments and blindness into the cultural life (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…The results of the two-way ANOVA showed that TLD mainly strengthened the operation guiding area of the graphics; under the representation mode where graphics are presented using lines, TLD adds texture to the operation area to the operation area. Krivec et al (2014) suggested that TLD is a good presentation method for tactile graphic simplification, but they only discussed one scale type. However, this study revealed that among the three scales (small, medium, and large), TLD is significantly better than LD under the medium scale because when using the TLD mode in the medium-scale operation area, the shape can be completely presented, which is helpful for identification (Kennedy & Bai, 2002).…”
Section: Identification Timementioning
confidence: 99%
“…The results of the two-way ANOVA showed that TLD mainly strengthened the operation guiding area of the graphics; under the representation mode where graphics are presented using lines, TLD adds texture to the operation area to the operation area. Krivec et al (2014) suggested that TLD is a good presentation method for tactile graphic simplification, but they only discussed one scale type. However, this study revealed that among the three scales (small, medium, and large), TLD is significantly better than LD under the medium scale because when using the TLD mode in the medium-scale operation area, the shape can be completely presented, which is helpful for identification (Kennedy & Bai, 2002).…”
Section: Identification Timementioning
confidence: 99%
“…Artworks digitization has found a rapid expansion in museums, where it represents a useful tool not only for the insiders, such as restorers and conservators but also for a wider audience as, for example, visually impaired people that can reconstruct the mental image of the work through haptic fruition. The possibility of creating touchable reproductions for blind people was explored from the early nineties favoring the replica of 3D objects, while the challenging creation of representation of 2D artworks such as paintings was mostly realized starting from high resolution images [ 15 , 16 , 17 , 18 ]. Such tactile reproductions of 2D images introduce a bias in the interpretation of the original artwork [ 19 ].…”
Section: Introduction and Backgroundmentioning
confidence: 99%
“…On the other hand, packages need to contain information which communicates [3] how to appropriately store and use the product, and how to transport or recycle the package. Many packages, especially in the pharmaceutical industry, also require the text in Braille format to inform blind or partially sighted users [4][5][6][7]. Frequently, Braille characters appear over the text for sighted users.…”
Section: Introductionmentioning
confidence: 99%